Government Procurement : Market Access, Transparency, and Multilateral Trade Rules - Evenett, Simon J.; Hoekman, Bernard M. (World Bank, Washington, DC, 2013)
The authors examine the effects on national welfare and market access of two public procurement practices-discrimination against foreign suppliers of goods and services and nontransparency of the procedures used to allocate government contracts to firms. Both types of policies have become prominent in international trade negotiations, including the Doha Round of the World Trade Organization (WTO) trade talks. Traditionally, the focus of international trade agreements has been on market access. However, many developing countries have opposed the launch of negotiations to extend the principle of nondiscrimination to procurement. As a result, the current focus in the Doha Round is on an effort to launch discussions on agreeing to principles of transparency in procurement. While transparency will not constrain the ability of governments to discriminate in favor of domestic firms, it could nonetheless improve market access by reducing corruption. The authors assess and compare the impact of eliminating discrimination and fostering greater domestic competition in procurement markets and enhancing transparency in state contracting. Their analysis concludes that greater domestic competition on procurement markets and greater transparency will improve economic welfare. But there is no clear-cut effect on market access of ending discrimination or improving transparency. This mismatch between market access and welfare effects may account for the slower progress in negotiating procurement disciplines in trade agreements than for traditional border measures such as tariffs, given that market access is the driving force behind trade agreements.